Development and testing of a high-risk behavior scale for swimming among Chinese adolescents - Lu, Chao; Shi, Jiaxin; Zhang, Hui (Frontiers in Psychology, 2026)
BackgroundTeenagers are the main victims of drowning, and high-risk behavior is the main cause of drowning. However, there are no reliable and valid instruments for measuring these behaviors in China.ObjectiveThis study aimed to provide a measurement tool for measuring the high-risk behavior of swimming among adolescents in China. The adolescent swimming risk behavior scale was developed and tested for reliability and validity.Participants and settingThis study used stratified sampling to ensure sample representativeness. Stratification variables included educational level (elementary school, secondary school) and geographical region (areas with differing levels of economic development), thereby capturing key differences in age maturity and social environment. Among schools selected based on the aforementioned stratification variables, questionnaires were administered to eligible students (aged 10–19 years old, capable of swimming continuously for over 25 m).MethodsThis study assessed the internal consistency, factor structure (i.e., exploratory and validation factor analyses), and convergent and discriminant validity of the adolescent swimming risk behavior scale.ResultsThe findings suggest that the scale is a relatively reliable measure for assessing high-risk behavior in adolescent swimmers. Exploratory and validation factor analyses confirmed the four-factor structure, confirming the 20-item version of the scale, which obtained good internal consistency reliability. The internal consistency coefficient, Cronbach’s α, for the formal scale ranged from 0.764 to 0.869, with the total scale Cronbach’s α value being 0.859.ConclusionThe adolescent swimming risky Behavior Scale has high reliability and validity and is suitable for measuring adolescent swimming risky behavior in China.